Perancang Alat Sistem Monitoring Volume Air Pada Tangki Air Berbasis Telegram Dengan Mikrokontroler NodeMCU - Junaldi - -; Titin Ritmi -; Adityo Ferry - (Jurnal Ilmiah Poli Rekayasa, 2020)
At this time the world is experiencing a Covid-19 outbreak which has resulted in all activities being restricted and must implement health protocols to prevent the transmission of the corona virus. One of these health protocols is washing hands regularly. Padang State Polytechnic is an educational institution that applies health protocols by providing water tanks in several places so that everyone who comes to Padang State Polytechnic can wash their hands easily. The water tank available at the Padang State Polytechnic does not have a specific schedule for filling it. This causes the officer in charge to always check the condition of the water tank. At the Padang State Polytechnic, the number of water tanks available is not small. Periodic inspection of the water tank becomes ineffective and causes not all of the water to be fully filled or that there is also a tank that is not filled. Therefore, the Water Volume Monitoring System tool in a Telegram Based Water Tank with a NodeMCU Microcontroller can make it easier for officers to monitor the state of the water via telegram so that the water tank monitoring process at Padang State Polytechnic becomes more effective. The water volume monitoring system tool is built with NodeMCU Microcontroller technology and the Telegram application to check notifications.